Local Tradition and Harmony among Religious Adherents: the Dominant Culture of Hindu-Muslim Relation in Jembrana Bali - Saihu Saihu (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2020)
This study discusses the harmony of Hindu-Muslim’s local traditions in Jembrana, western Bali. This anthropology study employs Bruner's dominant cultural theory approach to see the practice of harmony in local communities. This study focuses on several local Hindu-Muslim traditions in Jembrana, which reflect harmony among religious communities, namely the tradition of ngejot, makepung, male, and rebana (tambourine). The ethnographic study confirms the importance of respect for the dominant culture carried out by the Muslim minority when implementing their religious traditions. Although the tradition of male and rebana, for instance, are Islamic traditions, Balinese Muslims adapted to Balinese customs as the dominant culture. They understood their positions to maintain and respect the dominant Balinese culture performed by the majority of Hindus in Jembrana. Balinese Hindus tried to show an excellent response to the Muslims by involving them in the local Balinese tradition even with the adaptation of their rituals. It is a wealth of local tradition that shows religious harmony portrait in Indonesia.